Decoration of a bio-inspired carbon nanosphere with Pt nanoparticles via a polymer-assisted strategy for enhanced electrocatalytic activity. (March 2015) - Kim, Gil-Pyo; Bae, Seongjun; Lee, Minzae; Don Song, Hyeon; Yi, Jongheop
Abstract: Despite the significant advances in nanostructured supporting materials used for metal-based catalysts, intractable problems including poor dispersion and the agglomeration of metal nanoparticles (NPs) within their complicated structure limit the practical applications. We report herein on a facile polyethyleneimine (PEI)-assisted strategy for the high dispersion and controllable coverage of Pt catalysts onto a 3-dimensional mesoporous carbon material, referred to as a "bio-inspired carbon nanosphere (BCN)". The PEI adsorbed on the carbon surface serves as anchoring sites for metal ions and as templates for metal nanoparticle growth. The resulting spherical Pt NPs are highly dispersed on the surface to the center of the BCN without any agglomeration even after a thermal annealing. The amount of loaded Pt can be adjusted from 7.3 to 27.7 wt% independently, which can be easily controlled by adjusting the precursor concentrations. Given their open pore structures and large surface area, Pt/BCN composites exhibit promising properties for use as electrocatalysts with high electrochemical active surface areas (84.9 m 2  g −1 ) and oxygen reduction reaction activity. The results suggest that this strategy can be widely applied to the deposition of metal NPs on highly controlled 3-D nanostructures. Graphical abstract: Highlights: BCN is decorated with Pt nanoparticles via PEI-assisted strategy. PEI serves as anchoring sites for metal ions and templates for metal growth. The Pt loading amounts can be controlled by varying the precursor concentration. PEI grafted on the carbon surface is removed by annealing process. Pt/BCN composites exhibit promising properties for an electrocatalyst.